Bla ma rgyaṅ ʼbod kyi gsol ʼdebs mos gus sñiṅ gi gzer ʼdebs źes bya ba bźugs so - Koṅ-sprul Blo-gros-mthaʼ-yas, 1813-1899 (s.n., 1972)
Devotional verses (adhyeṣaṇa) invoking the blessings of the religious preceptor.